Analysis of the giant genomes of Fritillaria (Liliaceae) indicates that a lack of DNA removal characterizes extreme expansions in genome size. Issue 2 (8th June 2015) - Kelly, Laura J.; Renny‐Byfield, Simon; Pellicer, Jaume; Macas, Jiří; Novák, Petr; Neumann, Pavel; Lysak, Martin A.; Day, Peter D.; Berger, Madeleine; Fay, Michael F.; Nichols, Richard A.; Leitch, Andrew R.; et al.
Summary: Plants exhibit an extraordinary range of genome sizes, varying by > 2000‐fold between the smallest and largest recorded values. In the absence of polyploidy, changes in the amount of repetitive DNA (transposable elements and tandem repeats) are primarily responsible for genome size differences between species. However, there is ongoing debate regarding the relative importance of amplification of repetitive DNA versus its deletion in governing genome size. Using data from 454 sequencing, we analysed the most repetitive fraction of some of the largest known genomes for diploid plant species, from members of Fritillaria . We revealed that genomic expansion has not resulted from the recent massive amplification of just a handful of repeat families, as shown in species with smaller genomes. Instead, the bulk of these immense genomes is composed of highly heterogeneous, relatively low‐abundance repeat‐derived DNA, supporting a scenario where amplified repeats continually accumulate due to infrequent DNA removal. Our results indicate that a lack of deletion and low turnover of repetitive DNA are major contributors to the evolution of extremely large genomes and show that their size cannot simply be accounted for by the activity of a small number of high‐abundance repeat families.